2012
DOI: 10.1017/s0022215112000606
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging features of large endolymphatic sac compartments: audiological and clinical correlates

Abstract: Objectives: (1) To study the prevalence and characteristics of large endolymphatic sac internal compartments on thin-section T2-and T2*-weighted magnetic resonance imaging, and to relate these to other large endolymphatic sac magnetic resonance imaging features, and (2) to correlate the compartment imaging features, endolymphatic sac size and labyrinthine anomalies with the patients' clinical and audiological data.Method: Magnetic resonance imaging studies for 38 patients with large endolymphatic sac anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous MR imaging studies have demonstrated that the enlarged ES contains different signal intensities on T1-or T2-weighted images compared with cerebrospinal fluid and other labyrinthine fluid. It has been considered that this is a consequence of the high protein concentration within the ES [32][33][34] . In human and animal protein concentration studies of the ES, the protein concentration of luminal fluid in the ES was shown to be markedly higher than that of the cochleo-vestibular endolymph and perilymph, even in LVA ears with SLC26A4 mutations, and creates a high osmotic gradient [35][36][37][38] .Thus, one possible explanation is that such high osmotic pressure and protein content may facilitate the penetration of the contrast agent into the endolymphatic sac, resulting in the high intensity signals for the ES and ED, particularly when the IV injection method is used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous MR imaging studies have demonstrated that the enlarged ES contains different signal intensities on T1-or T2-weighted images compared with cerebrospinal fluid and other labyrinthine fluid. It has been considered that this is a consequence of the high protein concentration within the ES [32][33][34] . In human and animal protein concentration studies of the ES, the protein concentration of luminal fluid in the ES was shown to be markedly higher than that of the cochleo-vestibular endolymph and perilymph, even in LVA ears with SLC26A4 mutations, and creates a high osmotic gradient [35][36][37][38] .Thus, one possible explanation is that such high osmotic pressure and protein content may facilitate the penetration of the contrast agent into the endolymphatic sac, resulting in the high intensity signals for the ES and ED, particularly when the IV injection method is used.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal area of the ES is known to contain a homogeneous substance that is believed to consist of macromolecular complexes composed of glycosaminoglycans, sulphated proteoglycans and glycoproteins [40 , 41] . Connor et al postulated that the low signal intensity compartment on T2-weighted MR images may correspond to these homogenous substances in the ES [34] . Therefore, the lower enhanced area on the MR images obtained using IV may imply the existence of a high protein compartment in the lumen of the ED and ES.…”
Section: Discussionmentioning
confidence: 99%